Measuring policy performance, democracy, and governance capacities: a conceptual and methodological assessment of the sustainable governance indicators (SGI) - Croissant, Aurel; Lott, Lars (European policy analysis, 2022)
This paper provides a critical assessment of the Sustainable Governance Indicators (SGI) and compares it with other prominent indices that address specific components of governance: V-Dem, WGI, and BTI. We offer a comparative assessment of content validity of these governance measures, their data generation processes, and their convergent validity. We conclude that the SGI’s most important contribution is the conceptualization of policy performance as a discrete index. Other relative strengths are the theoretical embeddedness and the exclusion of irrelevant meanings of governance, and the conceptualization of three governance components (Governance, Policy Performance, and Democracy). However, in terms of geographic and temporal coverage, the SGI is clearly inferior to WGI and V-Dem. The handling of third-party statistical data, the absence of uncertainty scores, and the (a-theoretical) aggregation of different indicators are additional shortcomings of the SGI. Finally, the SGI’s iterative process of expert deliberation has merits but is prone to biases.
Gesehen am 29.03.2023